2018
DOI: 10.21826/2446-8231201873307
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Dos Herbicidas Imazapir E Imazapique Na Comunidade Fitoplanctônica Em Lavoura De Arroz Irrigado

Abstract: RESUMO -Diante da toxicidade de herbicidas aos organismos aquáticos, comumente utilizados em lavouras de arroz irrigado, o presente trabalho visou avaliar o efeito toxicológico da mistura herbicida imazapir+imazapique (Kifi x ® ) e compostos isolados na comunidade fi toplanctônica utilizando mesocosmos. Os efeitos destes contaminantes foram avaliados por delineamento experimental em blocos ao acaso com esquema fatorial (5 x 3) e quatro repetições, totalizando 16 parcelas amostrais. Este estudo demonstrou pela … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In mesocosms, however, greater values of phytoplankton community richness were found in rice cultivated without the spraying of pesticides but with residual imidazolinone (151 species), such as in rice cultivated with imazapyr and imazapic herbicides (60 genera, with 44 genera observed by us), according to Cassol et al (2013) and Reck et al (2018), respectively. Baert et al (2016) exposed the plankton diatom community at different levels of richness to different concentrations of atrazine herbicide and observed that more diverse communities were less affected by herbicide stress.…”
Section: Phytoplankton and Epiphyton Associated With Cultivation Systemsmentioning
confidence: 68%
See 4 more Smart Citations
“…In mesocosms, however, greater values of phytoplankton community richness were found in rice cultivated without the spraying of pesticides but with residual imidazolinone (151 species), such as in rice cultivated with imazapyr and imazapic herbicides (60 genera, with 44 genera observed by us), according to Cassol et al (2013) and Reck et al (2018), respectively. Baert et al (2016) exposed the plankton diatom community at different levels of richness to different concentrations of atrazine herbicide and observed that more diverse communities were less affected by herbicide stress.…”
Section: Phytoplankton and Epiphyton Associated With Cultivation Systemsmentioning
confidence: 68%
“…In the CF, the values of pH and dissolved oxygen were close to the ones registered in the Ibirapuitã River (7.1 -9.1 and 7.02 -9.06 mg L -1 , respectively) in 2018, according to the ANA (2018). The water pH ranging from slightly acidic to neutral from the CF is similar to that of mesocosms that underwent herbicide spraying and the control treatment (Reck et al 2018;Reimche et al 2015).…”
Section: Organic Versus Conventional Farmingmentioning
confidence: 75%
See 3 more Smart Citations